Pengembangan Modul Pembelajaran Berdiferensiasi Kurikilum Merdeka Berdasarkan Jenjang, Materi Dan Model Pembelajaran (Mathematical Proceedings of The Widya Mandira Catholic University, 2024)
The aim of this research is to describe how differentiated learning teaching modules are implemented in schools, to answer research questions related to levels, materials and learning models in the implementation of differentiated learning teaching modules that have been implemented. This research uses a Literature Review with steps: developing research question, developing the search strategy (searching for articles or literature that match the research theme), selection criteria (applying inclusion criteria to select articles), evaluation and analysis data and interpreting (reporting research findings). A total of 20 articles were found and after selection there were 15 articles that met the inclusion criteria for analysis. The result of the research show that the application of differentiated learning teaching modules can be developed at the elementary, middle school, high school levels and at school principals and driving teachers. The materials use in implementing the differentiated learning teaching module include: algebraic forms, linear equations, LCM, FPB, Integrals and Circles. But the majority of studies use circle material at the junior high school level. The majority of studies use contextual learning models. Suggestions for future researchers to conduct further research regarding the implementation of independent curriculum differentiated learning-based teaching modules at high school level both in terms of material and learning models used in learning